STUDI NORMATIF TENTANG PENGGUNAAN JUSTICECOLLABORATOR DALAM MENGUNGKAP TINDAK PIDANAKEJAHATAN NARKOTIKA - MADJEN SILABAN (2020)
The Law research was conducted to find out the concepts and benefits of using justice collaborator mechanisms in uncovering narcotics crimes in Indonesia with applicable laws and how to optimize the role and provide protection of Justice collaborators in the fight against narcotics crime in Indonesia. The research method uses normative juridical study that bases on the laws and regulations related to the research theme. The results of the study can be explained that the concept of Justice collaborator, has been widely mentioned in various laws and regulations, such as in Law Number 7 of 2006 concerning Ratification of the United Nations Convention Against Corruption, Law Number 5 of 2009 concerning Ratification of the United Nations Conventions Against Transnational Organized Crime (United Nations Convention Against Organized Transnational Crime), Law Number 31 of 2014 concerning Witness and Victim Protection, Supreme Court Circular Letter (SEMA) Number 4 of 2011), Joint Regulations of Kemenkumham, Polri, Attorney General's Office, Attorney General, KPK and LPSK in 2011. Then, it can be explained that the mechanism of using justice collaborator has an important role and benefits in dismantling narcotics crime, this is because Justice collaborator has access to the narcotics network even though the risk faced by Justice collaborator is also high. Therefore, witnesses of justice collaborators who want to work together in uncovering and dismantling narcotics networks need to get legal protection, special handling and appreciation.